Toward Eco‐Friendly Lead‐Free Low‐Dimensional Perovskites. Issue 7 (26th April 2022) - Gao, Xinying; Luo, Jiawei; Wu, Yilei; Lu, Aini; Ju, Ming-Gang; Wang, Jinlan
Abstract : Lead halide perovskites are regarded as potential successor of traditional perovskites, due to their variable structures and excellent optoelectronic properties. However, its large‐scale commercialization is impeded by the inherent instability and toxicity. In this regard, lead‐free low‐dimensional perovskites (LFLDPs) have emerged as promising alternatives to the traditional 3D components, due to their structural tunability and environmental friendliness and stability. The structure–property characteristics of LFLDPs endow them with a unique combination of optoelectronic efficiency and versatile functionality, which has led to their impressive employment in the optoelectronic devices. In this perspective, a brief description of recent progress on the various LFLDPs, and especially from theoretical perspective, is presented. First, the general types of LFLDPs are introduced and the metal elements that have been used to date in the exploitation of LFLDPs are collected. This is followed by a discussion of fundamental understanding of the structure–property relationship for different dimensional perovskites in the view of connectivity and element composition. Finally, luminescence mechanism of relevant LFLDPs and the key frontiers and challenges for further developing LFLDP materials is discussed. Abstract : Lead‐free low‐dimensional perovskites (LFLDPs) emerge as promising alternatives to the traditional 3D perovskites, due to their structural tunability, environmental friendliness, and stability. The structure–property relationship of lead‐free low‐dimensional perovskites (LFLDPs) endows them with a unique combination of peculiar optoelectronic properties and versatile functionalities, which have led to their impressive employment in the photovoltaic and optoelectronic devices.